Rubber tree transpiration in the lowlands of Sumatra. Issue 7 (17th July 2017) - Niu, Furong; Röll, Alexander; Meijide, Ana; Hendrayanto,; Hölscher, Dirk
Abstract: The expansion of rubber cultivation in Southeast Asia raises concerns about the integrity of the hydrological cycle. From mainland Asia, high evapotranspiration from rubber plantations was reported. Our study was conducted in the Sumatran lowlands (Indonesia), where rubber is grown by small holders under maritime climate. We assessed patterns of water use with sap flux methods, focusing on influences of tree age and size. We first tested a field measurement scheme in methodological experiments and subsequently applied it to 10 plots in monocultural rubber plantations. Among fully leaved, mature stands, maximum sap flux densities decreased with increasing tree diameter in 14‐ and 16‐year‐old plantations, but not in 7‐ and 8‐year‐old ones. Consequently, tree water use increased more steeply with increasing diameter in the younger than in the older plantations. In contrast to this, among the same five mature plantations, stand‐scale transpiration decreased with increasing mean tree diameter and height. This was due to a negative linear relationship between diameter and stand density. Among seven fully leaved plantations, stand age explained 95% of the site‐to‐site variability in transpiration. Temporally, rubber transpiration showed pronounced seasonality due to leaf shedding. Transpiration in our study was substantially lower than in rubber plantations in mainland Asia; reasons include differences in methods, management, and climate. In Sumatra, rubber may be ecohydrologically less concerning than, for example, oil palm plantations, due to low transpiration and periodical leaf shedding. Our study endorses the importance of considering age, management, climate, and species in ecohydrological assessments of tropical plantation landscapes.